CBIO-10. REDUCED IRON EXPORT FUNCTIONS IN A CELL INTRINSIC MANNER TO DRIVE GLIOBLASTOMA GROWTH. (9th November 2020) - Troike, Katie; Mulkearns-Hubert, Erin; Silver, Daniel; Connor, James; Lathia, Justin
Abstract: Glioblastoma (GBM), the most common primary malignant brain tumor in adults, is characterized by invasive growth and poor prognosis. Iron is a critical regulator of many cellular processes, and GBM tumor cells have been shown to modulate expression of iron-associated proteins to enhance iron uptake from the surrounding microenvironment, driving tumor initiation and growth. While iron uptake has been the central focus of previous investigations, additional mechanisms of iron regulation, such as compensatory iron efflux, have not been explored in the context of GBM. The hemochromatosis ( HFE ) gene encodes a transmembrane glycoprotein that aids in iron homeostasis by limiting cellular iron release, resulting in a sequestration phenotype. We find that HFE is upregulated in GBM tumors compared to non-tumor brain and that expression of HFE increases with tumor grade. Furthermore, HFE mRNA expression is associated with significantly reduced survival specifically in female patients with GBM. Based on these findings, we hypothesize that GBM tumor cells upregulate HFE expression to augment cellular iron loading and drive proliferation, ultimately leading to reduced survival of female patients. To test this hypothesis, we generated Hfe knockdown and overexpressing mouse glioma cell lines. We observed significant alterations in the expression of several iron handling genes with Hfe knockdown or overexpression, suggesting global disruption of iron homeostasis. Additionally, we show that knockdown of Hfe in these cells increases apoptosis and leads to a significant impairment of tumor growth in vivo . These findings support the hypothesis that Hfe is a critical regulator of cellular iron status and contributes to tumor aggression. Future work will include further exploration of the mechanisms that contribute to these phenotypes as well as interactions with the tumor microenvironment. Elucidating the mechanisms by which iron effulx contributes to GBM may inform the development of next-generation targeted therapies.